Reforming intellectual property - Ghidini, Gustavo, 1941-; Falce, Valeria (Edward Elgar Publishing, 2022)
"Reforming Intellectual Property brings together 19 of the world's leading scholars in the field to offer their unique insight into the future of intellectual property. Providing a diverse array of perspectives on the most pressing reforms needed in the current IP regime, whether in terms of legislation at national and international levels, or interpretation of existing law, this exceptional book highlights the key issues in this area and sets out an agenda for future research and policy. Examining the question of what changes to IP law and policy are most urgent and would have the most impact, chapters cover a wide range of subjects, with some focusing on specific topics such as the reform of non-traditional trademarks, or the fair use and research exemption in patent law. Other contributions take a broader approach, such as a reappraisal of performers' rights in audio and audiovisual media that encompasses implications for creativity, welfare and ethics in the film industry, and a proposal for the creation of an International Intellectual Property Treaty. This book will prove to be crucial reading for all scholars and students of IP law, as well as policymakers and practitioners in the field. It will also be of interest to researchers working in related fields such as competition and human rights law for its intersecting analysis of these areas"--